Compact Hexagonal Monopole Antenna for Lower 5G Bands - Alsaif, H. (Engineering, Technology & Applied Science Research, 2019)
This paper presents a compact planar antenna with extreme wide band. The antenna is designed to cover the entire lower 5th generation operating bands ranging from 2.32GHz to more than 12GHz. This band also covers the IEEE 802.11 a/b/g/n/ac. The patch geometry has been simulated using an industrial standard simulation software called CST MWS. The monopole is miniaturized with a total size of 23x24x1.2mm3. The radiator and the ground plane are printed on a substrate of Rogers Duriod RT 5880 with relative permittivity of 2.2 and loss tangent of 0.00009. The simulated reflection coefficient and radiation pattern results are presented. S11 parameter for the designed antenna is less that -10dB over the operating band, with lowest value of -32.5dB at 2.85GHz. The radiation pattern is presented at the two orthogonal planes, elevation (E plane) and azimuth (H plane). Simulated results show that the antenna is appropriate of lower 5G bands application and several other wireless systems.